2001
DOI: 10.1091/mbc.12.9.2629
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic Acid (DCA) Causes Ligand-independent Activation of Epidermal Growth Factor Receptor (EGFR) and FAS Receptor in Primary Hepatocytes: Inhibition of EGFR/Mitogen-activated Protein Kinase-Signaling Module Enhances DCA-induced Apoptosis

Abstract: Previous studies have argued that enhanced activity of the epidermal growth factor receptor (EGFR) and the mitogen-activated protein kinase (MAPK) pathway can promote tumor cell survival in response to cytotoxic insults. In this study, we examined the impact of MAPK signaling on the survival of primary hepatocytes exposed to low concentrations of deoxycholic acid (DCA, 50 microM). Treatment of hepatocytes with DCA caused MAPK activation, which was dependent upon ligand independent activation of EGFR, and downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
214
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(235 citation statements)
references
References 81 publications
20
214
0
1
Order By: Relevance
“…On the other hand, anti-TRAIL antibody very weakly blocked the apoptosis (Figure 6b). Several studies have reported that death receptors such as Fas and TNF-R can induce apoptosis in a ligand-independent manner (Beltinger et al, 1999;Fumarola et al, 2001;Qiao et al, 2001). Furthermore, DR5 is also believed to be able to induce ligand-independent apoptosis (Sheikh and Huang, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, anti-TRAIL antibody very weakly blocked the apoptosis (Figure 6b). Several studies have reported that death receptors such as Fas and TNF-R can induce apoptosis in a ligand-independent manner (Beltinger et al, 1999;Fumarola et al, 2001;Qiao et al, 2001). Furthermore, DR5 is also believed to be able to induce ligand-independent apoptosis (Sheikh and Huang, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The detergent properties of DCA (but not CA) cause membrane perturbations leading to the release of arachidonic acid, which is converted by the enzymes cyclooxygenase 2 (COX-2) and lipooxygenase, to proinflammatory and pro-angiogenic prostaglandins, and reactive oxygen species which damage DNA and inhibit DNA repair enzymes. 87,88 DCA also induces COX-2 expression through transactivation of the epidermal growth factor receptor, 87,89 and activates the b-catenin cell-signaling pathway resulting in colon cancer cell proliferation and invasiveness. 90 Notably, a large body of published work demonstrates the effectiveness of non-steroidal anti-inflammatory drugs in significantly reducing polyp formation and reducing CRC risk by inhibiting the activity of COX-2.…”
Section: Deoxycholic Acid and Colon Cancermentioning
confidence: 99%
“…Indeed, we and others have previously reported that EGF induces proliferation [20] and protects hepatocytes from various apoptotic insults, including TGF-β, Fas, and deoxycholic acid [25,35,36].…”
Section: It Is Well Known That Egfr-dependent Signalling Integrates Pmentioning
confidence: 82%